2020
DOI: 10.1182/blood-2020-138842
|View full text |Cite
|
Sign up to set email alerts
|

Older Age and Increased Neutrophil-to-Lymphocyte Ratio (NLR) Are Predictors of Mortality in a Multiethnic Urban Cohort of Hematologic Neoplasms and COVID-19 Patients

Abstract: Introduction: We sought to compare outcomes among patients with hematologic neoplasms diagnosed with COVID-19 infection in a multiethnic urban academic medical center. Methods: A retrospective analysis of patients with hematologic neoplasms diagnosed with COVID-19 from March 17th to June 8th2020 was conducted. Subjects included were censored at last point of contact. Variables collected included age, gender, race/ethnicity, hematologic diagnosis, cancer treatment st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It should be noted that in previous studies, it has been reported that NLR is an inflammatory index directly related to age in healthy individuals and COVID-19 patients ( 28 , 29 ). The difference in the studied population or the sample size is the possible reason for the difference between the results of the previous studies and the current study's findings.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted that in previous studies, it has been reported that NLR is an inflammatory index directly related to age in healthy individuals and COVID-19 patients ( 28 , 29 ). The difference in the studied population or the sample size is the possible reason for the difference between the results of the previous studies and the current study's findings.…”
Section: Discussionmentioning
confidence: 89%
“…These include C-reactive protein, interleukin-6 (IL-6), TNF-alpha, ferritin, and D-dimer. In addition, abnormalities in the complete blood count, including low platelets, low or high absolute lymphocyte count, high absolute neutrophil count, and increased neutrophil-to-lymphocyte ratio, have been associated with worse COVID-19 outcomes [ 31 ]. As patients with hematologic malignancies have complete blood count abnormalities associated with their diseases, the independent effects of complete blood count abnormalities and hematologic malignancies on COVID-19 outcomes are not well-understood.…”
Section: Noncancer-related Risk Factorsmentioning
confidence: 99%